The Impact of Service Innovation, Total Quality Management, and Technology Adoption on Competitiveness and Its Effects on the Performance of Third-Level Military Health Center Hospitals - Yuliaty, Farida; Kosasih, Kosasih; Rosady, Faisal; Erlambang, Rio Yoga; Amin, Hayat (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the influence of service innovation, total quality management (TQM), and technology adoption on competitiveness and their subsequent impact on the performance of third-level military health center hospitals. A quantitative research approach was employed, using a survey method to collect data from hospital leaders and staff members. The data were analyzed using Structural Equation Modeling (SEM) to test the relationships among variables. The results indicate that service innovation, TQM, and technology adoption significantly enhance hospital competitiveness. Furthermore, competitiveness was found to mediate the relationship between these strategic factors and hospital performance. The findings highlight the strategic importance of fostering innovation, quality management, and technological integration to improve operational efficiency and service quality in military hospital settings.